The study on user satisfaction on the adequacy of facility at Perpustakaan Sultan Badlishah UiTM Kedah / Mastura Mat Daud - Mat Daud, Mastura (2010)
Library is the important place which Is can be known as an information resources centre. The entire libra,y has to make sure all the provisions on their materials and resources can make satisfaction of the user. The library adequacy was needed in order lo measures the satisfaction of the library users on the library facilities. The library adequacy can be known as a satisfactory or acceptable in using the library or any material from the library. Therelore, a study on the user satisfaction on adequacy of library facility was conducted. The library is from the academic library which Is located at UiTM Kedah. The respondents of this study generally among the bachelors student of UiTM Kedah. The objective of this study is to study the relationships between dependent variables and independent variables which are consist of equipments, furniture and library space. The study believes that user satisfaction is dependent variable. This variable is believed lo innuence the independent variable. The finding stated that most ol the respondents are satisfied with the adequacy of library lacilities which is being as highest percentage that is representing 73.2'14 with 93 respondents. Then, it followed by respondent which are not satisfied where representing 26.8% with 3"4 respondents. The recommendations are included for library to make a new improvements and continuing a lurther research based on the previous study to expand and gains future informative in research that will lead to the development of new knowledge and help llbrary Industry to grow up In terms of proving Information.